2015
DOI: 10.1093/imammb/dqv013
|View full text |Cite
|
Sign up to set email alerts
|

Computed tear film and osmolarity dynamics on an eye-shaped domain

Abstract: The concentration of ions, or osmolarity, in the tear film is a key variable in understanding dry eye symptoms and disease. In this manuscript, we derive a mathematical model that couples osmolarity (treated as a single solute) and fluid dynamics within the tear film on a 2D eye-shaped domain. The model includes the physical effects of evaporation, surface tension, viscosity, ocular surface wettability, osmolarity, osmosis and tear fluid supply and drainage. The governing system of coupled non-linear partial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 84 publications
2
37
0
Order By: Relevance
“…Various mathematical models, as summarized and furthered by Braun et al, have stated that the osmolarity across the ocular surface is different to that measured in the tear meniscus [153]. During the blink interval the tear film thins over the cornea, mainly due to evaporation, leading to a hyperosmotic shift [153,154]. The level of hyperosmotic shift depends on the thinning rate, which is driven by the evaporation rate [154].…”
Section: Biophysical Measurements Of the Tear Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…Various mathematical models, as summarized and furthered by Braun et al, have stated that the osmolarity across the ocular surface is different to that measured in the tear meniscus [153]. During the blink interval the tear film thins over the cornea, mainly due to evaporation, leading to a hyperosmotic shift [153,154]. The level of hyperosmotic shift depends on the thinning rate, which is driven by the evaporation rate [154].…”
Section: Biophysical Measurements Of the Tear Filmmentioning
confidence: 99%
“…During the blink interval the tear film thins over the cornea, mainly due to evaporation, leading to a hyperosmotic shift [153,154]. The level of hyperosmotic shift depends on the thinning rate, which is driven by the evaporation rate [154]. In the event of a low thinning rate, such as 1 μm/min, tear film osmolarity over the ocular surface will increase from 300 mOsm/L to 332 mOsm/L over a 25 s period, but will increase to 1830 mOsm/L in the case of a rapid thinning rate of 20 μm/min [153].…”
Section: Biophysical Measurements Of the Tear Filmmentioning
confidence: 99%
“…In this section, the diffusivity of salt and fluorescein are assumed equal and to be that of the salt value from Zubkov et al (2012), and the isotonic osmolarity is 302 mOsM. We focus on results for the thickness, osmolarity (Li et al, 2014a) and fluorescence distributions over the exposed ocular surface shown in Figs. 23 and 24.…”
Section: Interblinkmentioning
confidence: 99%
“…The flux of fluid entering the domain is a sum of influx from the lacrimal gland ( lg ) and efflux via the puncta ( p ). They are complicated functions that are given elsewhere (Li et al, 2014a, 2014b). The flux boundary condition is shown at specific times in Fig.…”
Section: 1 Mathematical Model Parametersmentioning
confidence: 99%
“…Ocular mucus helps maintain the wettability of the ocular surface and provides lubrication for lid movements over it 2 . In the healthy eye, the glycocalyx, which has previously been referred to as the mucus layer, prevents the epithelial surface from dewetting 3 . Consistent with the current understanding of tear function, the fluorescein tear break up time test devised by Norn 4 was originally intended to be used as a measure of mucus efficiency or deficiency.…”
mentioning
confidence: 99%